STRATEGI KOMUNIKASI DINAS PENGENDALIAN PENDUDUK KELUARGA BERENCANA PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KABUPATEN KAMPAR MENUJU KOTA LAYAK ANAK TINGKAT UTAMA - Ilham Raka Guntara; Tantri Puspita Yazid; Rumyeni Rumyeni (Universitas 17 Agustus 1945 Semarang, 2023)
Child-worthy cities are the first terms introduced by the ministry of women's empowerment state in 2005 through a suitable city policy for children. In policy, it explains that the kla is the district/city government's effort to accelerate the implementation of the convention on the rights of the child (CRC) from legal frameworks in definitions, development and interventions, such as appropriate policies, institutions, and programs for children. Kla is kabupten/city has a child-based development system through integration of commitments and government resources, business communities and comprehensive policies planned and sustainable, programs and activities to fulfill the child's rights. On the kla administration, the kampar district also involves local government agencies and communities. The study USES qualitative methods, the data-gathering techniques used in this research interviews, observation, and documentation. As for the subject of the informant, who has been selected using this type of information, the research of 11 informals. that is, the kasubag child protection, the children's forum, the kampar children's ambassador, 4 parents, 2 school students, 3 teachers.